(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Employees have an important role in carrying out company strategy in order to achieve company goals. For this reason, good performance is needed from these employees. Increasing employee capabilities can be achieved by holding training to increase the potential of the company’s Human Resources. The purpose of this research is to determine the effect of soft skills, hard skills and life skills training on employee performance at PT. Bank Negara Indonesia (PERSERO) Tbk Kotamobagu Branch. This research is quantitative research by giving questionnaires to 50 respondents. This research uses data analysis such as validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination tests and hypothesis tests. The results of this research show that: (1) Soft skills training, hard skills training and life skills training together have a significant influence on employee performance at PT. Bank Negara Indonesia Kotamobagu Branch. (2) Soft skills training has a positive and significant effect on employee performance at PT. Bank Negara Indonesia Kotamobagu Branch. (3) Hard skills training has a positive and significant effect on employee performance at PT. Bank Negara Indonesia Kotamobagu Branch. (4) Life skills training has a positive and significant effect on employee performance at PT. Bank Negara Indonesia Kotamobagu Branch.